2019
DOI: 10.1007/s10803-019-04046-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Prolonged-Release Melatonin for Sleep in Children with Autism Spectrum Disorder: Impact on Child Behavior and Caregiver’s Quality of Life

Abstract: A randomized, 13-weeks, placebo-controlled double-blind study in 125 subjects aged 2–17.5 years with Autism Spectrum Disorder or Smith-Magenis syndrome and insomnia demonstrated efficacy and safety of easily-swallowed prolonged-release melatonin mini-tablets (PedPRM; 2–5 mg) in improving sleep duration and onset. Treatment effects on child behavior and caregiver’s quality of life were evaluated. PedPRM treatment resulted in significant improvement in externalizing but not internalizing behavior (Strengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 55 publications
(73 reference statements)
4
64
0
4
Order By: Relevance
“…This study thus corroborates the interest of the longest sleep episode as a marker of sleep quality related to daytime outcomes in children with ASD. In accordance with these results, a previous study found that a clinically meaningful improvement in the duration of the longest sleep episode, after a 13-week treatment of pediatric prolonged-release melatonin, led to a significant improvement in daytime behavioral problems in a population of 125 ASD children aged 2-17.5 years [46]. Additionally, this study found that the longest sleep episode was also associated with improvement in quality of life in parents.…”
Section: Discussionsupporting
confidence: 88%
“…This study thus corroborates the interest of the longest sleep episode as a marker of sleep quality related to daytime outcomes in children with ASD. In accordance with these results, a previous study found that a clinically meaningful improvement in the duration of the longest sleep episode, after a 13-week treatment of pediatric prolonged-release melatonin, led to a significant improvement in daytime behavioral problems in a population of 125 ASD children aged 2-17.5 years [46]. Additionally, this study found that the longest sleep episode was also associated with improvement in quality of life in parents.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with repetitive behaviors, but not restrictive behaviors like the insistence on routine, experienced significant reported sleep problems even after controlling for anxiety ( Hundley et al, 2016 ). This suggests that melatonin may be better suited as an intervention for the subset of ASD patients with repetitive behaviors and sleep problems ( Schroder et al, 2019 ). Understandably, the work in patients is focused on treating the symptoms rather than understanding the underlying biology.…”
Section: Discussionmentioning
confidence: 99%
“…Schroder et al found that ASD patients managed with prolonged release of melatonin showed improvement in externalizing behavior. This was measured by the strength and difficulty questionnaire (SDQ) with a treatment difference of -0.74 but was statistically not significant (P = 0.076) [25]. This study did find that melatonin at a higher dose above 10 mg is also not efficacious in improving sleep quality [25].…”
Section: Efficacymentioning
confidence: 75%
“…Five studies conducted in an outpatient setting evaluated the efficacy of melatonin on sleep patterns in ASD [21][22][23][24][25]. Double-blinded-RCT (DB-RCT) conducted by Maras et al included 95 pediatric patients with ASD and 51 patients received prolonged-release melatonin (2-10 mg/day) for 52 weeks and compared with placebo (N = 44).…”
Section: Efficacymentioning
confidence: 99%